Attitudes of doctors and nurses towards task-shifting of male circumcision to nurses in Swaziland - Jonasi, Solomon (My University, 2014)
Background: Male circumcision (MC) has a substantial effect in reducing HIV infections in men by 60 -70% making it one of the best available evidence-based biomedical HIV prevention interventions. Swaziland included Voluntary Medical Male Circumcision (VMMC) as part of its comprehensive HIV prevention package but the national scale up has been constrained by the limited availability of trained physicians, who are the only professionals permitted to perform the surgery. Task-shifting has been proposed as a possible strategy to increase service providers in the face of HIV and AIDS and the human resource for health crisis. Study Aim: The aim of this study was to determine the attitudes of doctors and nurses towards task shifting of male circumcision procedures to nurses in 2012. Methodology: A cross-sectional, descriptive survey was carried out. A self-administered questionnaire with close-ended rating and reverse coded questions was distributed to all nurses and doctors affiliated to the non-governmental organization (NGO), governmental, missionary and privately-run VMMC clinics nationwide. Data from returned questionnaires were entered, cleaned and analyzed using Statistical Package for Social Science (SPSS) version 22 and Microsoft Excel. Analysis of the internal reliability of the questionnaire scale and sub-scales was conducted. The main statistical procedures were descriptive statistics and tests of association. Results: The study recruited 398 participants (25.4% doctors and 74.6% nurses), of which 44.2% were male and 56% were Swaziland nationals. This study found that 80.4% of the participants (doctors and nurses) had a positive attitude towards the reform of task-shifting VMMC to nurses. Nurses had a more positive attitude than doctors (p<0.001), while male nurses had a significantly more positive attitude than female nurses (p<0.001).However, there was no significant difference between the attitudes of male and female doctors (p=0.130). The study found that sex (p=0.001), profession (doctor vs. nurse) (p<0.001), nationality (expatriate vs. local) (p<0.001) and having ever practically performed the surgical procedure (p<0.001) were significantly associated with the participants attitude. However, their primary role (administrator vs. clinician) (p=0.059) and time spent in the VMMC programme (p=0.112) did not significantly influence the participants’ attitude towards the task-shifting policy reform. Conclusions and Recommendations: Doctors and nurses in Swaziland generally have a positive attitude towards task-shifting of male circumcision to nurses. Nurses, males, participants with longer exposure and practical experience in VMMC, older participants and expatriates had even more positive attitudes towards the reform than their counterparts. The findings of the study suggest that the government should consider development of a task-shifting policy after further research that looks into determining attitudes of other stakeholders in VMMC and should also consider strategies to address the special groups that had lower or negative attitudes towards the reform than their counterparts, such as through sensitization campaigns. Feasibility, cost-effectiveness and other practical issues in our setting also need to be taken into consideration, including a possible trial (pilot). The reform should, however, be introduced with consideration of aspects of adequate training, development, supervision and support, administrative regulation, staff motivation and recognition.
A research report submitted to the School of Public Health, University of the Witwatersrand in partial fulfillment of the requirements for the degree of Master of Public Health 24th October, 2014
Keywords: Circumcision, Male